Stachybotrys citri sp. nov. and Volutella rauvolfii sp. nov. – two novel dematiaceous hyphomycetes from India - and A.K. PANDEY, RASHMI DUBEY* (Indian Phytopathology, 2013)
During a survey of microfungi from diversified habitats, two novel dematiaceous hyphomycetes were collected from the forest of Jabalpur. Stachybotrys citri sp. nov. possess smooth conidiophores with lower hyaline and the upper brownish part and also possess two types of conidia while Volutella rauwolfii sp. nov. has lobed & sessile sporodochia, hyaline setae and verrucose & subhyaline conidia.